Late presenters with ST-elevation myocardial infarction and thromboembolic complications: a treatment challenge: a case report - Małgorzata Wojciechowska; Karol Momot; Jakub Tomaszewski; Bartosz Walkowski; Dagmara Gralak-Łachowska; Krzysztof Wróbel; Dariusz Zieliński; Paweł Czub; Jakub Zieliński; Maciej Zarębiński (Journal of Medical Case Reports)
Abstract Background Late presenters with ST-elevation myocardial infarction pose a considerable challenge in the field of cardiovascular medicine. These individuals, who delay seeking medical attention after the onset of ST-elevation myocardial infarction symptoms, often face substantial difficulties in treatment. The coronavirus disease 2019 pandemic led to a significant increase in the number of late presenters. By increasing the frequency of complications such as thromboembolic events in the course of left ventricular thrombus, the pandemic necessitated the refinement of existing management strategies. Case presentation In this paper, we present two White male patients of Central European (Polish) descent (50 and 64 years old) who, although reported to have had acute ST-elevation myocardial infarction, turned out to be ST-elevation myocardial infarction latecomers. In both cases, we were dealing with the presence of left ventricular thrombus and complications related to the central nervous system. On the basis of these two patients, we discuss the role of revascularization in latecomer ST-elevation myocardial infarction patients. We present the position of direct oral anticoagulants in the left ventricular thrombus treatment and show that, in limited cases of a huge thrombus, cardiac surgery is a treatment of choice. Conclusions As left ventricular thrombus is still relatively common in ST-elevation myocardial infarction latecomers, we present the current state of knowledge on this topic, emphasizing the need for further research in this area.